Implementation of Death Penalty Crime: Dilemma between the Nationality Principle and Human Rights - Henry Yoseph Kindangen; H.S Tisnanta; Djoko Priyono (Universitas Lampung, 2022)
Extradition and prosecution are cornerstones of international law cooperation’s enforcement to prevent immunity from criminal responsibility, especially regarding the refusal to extradite nationals. The principle’s implementation in its development is influenced by the trend from abolitionist countries to refuse the requests for Mutual Legal Assistance in criminal matters (MLA) related to death penalty crimes. Guarantees from requesting the state not to impose death penalty sentences needs to implement nationality jurisdiction if the state refuses to extradite its citizens to another country. Countries that impose death penalty demonstrate that the nationality principle is very successful in investigating crimes committed abroad, whereas countries that have abolished the death penalty consider the nationality principle to be a violation of human rights. This paper focuses its discussion on the usefulness of Article 8 paragraph (5) of the Criminal Code Draft, which regulates the exceptional nature of the death penalty in the nationality principle’s implementation. This paper concludes that the exceptional nature of the death penalty in nationality principles' implementation is regulated in Article 8 paragraph (5) of the Criminal Code Draft. This Article elaborates that a country of hindered crime could prevent MLA requests from Indonesia related to death penalty crimes based on its international obligations and the perspective of human right. This research uses a normative approach and pragmatic-descriptive analysis.